The Influence of Adversity Quotient and Self-Efficacy on Students’ Qur’an Memorization Ability - Rohman, Taufikur; Ilyasin, Mukhamad; Suratman, Suratman (Pascasarjana Universitas KH. Abdul Chalim, 2026)
Memorizing the Qur’an is not merely a cognitive activity but also a psychological and spiritual process that requires strong mental endurance and self-confidence. In many Islamic boarding schools, students often face difficulties in maintaining consistency and achieving memorization targets, indicating that psychological factors play a crucial role in tahfiz success. This study aims to examine the influence of Adversity Quotient (AQ) and Self-Efficacy (SE) on students’ Qur’an memorization ability, both partially and simultaneously. The research employed a quantitative approach using an ex post facto correlational design. Data were collected from 157 students selected through proportional random sampling from three Islamic boarding schools in East Kalimantan. The instruments consisted of AQ and SE questionnaires based on Likert scales and a Qur’an memorization performance test assessed through tasmi’ sessions. Data were analyzed using multiple linear regression after passing normality, multicollinearity, and heteroscedasticity tests. The results indicate that AQ and SE simultaneously have a significant effect on students’ Qur’an memorization ability (F = 82.125, p < 0.05). Partially, both variables show positive and significant influences, with Adversity Quotient (β = 1.106) exerting a stronger effect than Self-Efficacy (β = 0.546). These findings demonstrate that psychological endurance and self-belief are key determinants of success in Qur’an memorization. The study implies that tahfiz education should not only focus on memorization techniques but also systematically integrate psychological resilience and confidence-building strategies to enhance students’ academic and spiritual achievement.